Reconstructing the Concept of Women's Rights and Duties in Islamic Marriage Law Based on the Principle of Gender Equality - Moh. Riziq (Universitas Sultan Ageng Tirtayasa, 2025)
The relationship between the rights and duties of husbands and wives in Islamic marriage law has been regulated as the foundation for the formation of a harmonious family. The Marriage Law and the Compilation of Islamic Law (KHI) mention the balance of rights and positions of husbands and wives, but still structurally differentiate the roles of husbands and wives, triggering tension between the principle of equality and patriarchal legal constructs. This article aims to reconstruct the concept of women's rights and duties in Islamic marriage law and examine its compatibility with gender equality. This study uses qualitative research with a descriptive approach through a literature study, analyzed using content analysis based on gender justice theory and maqashid al-shari'ah. This article argues that women's rights and duties are normatively just, but in practice they still reproduce gender-based hierarchical relations. Rigid role divisions have the potential to place women in subordinate positions. A reinterpretation and reconstruction of Islamic marriage law is necessary in order to reflect substantive gender equality and be in line with the objectives of sharia.